Prophylaxis against febrile neutropenia with pegfilgrastim in Italy: a budget impact analysis - Giovanni Rosti; Maria Lebboroni; Ario Cerchiari; Pablo Katz (Farmeconomia: Health Economics and Therapeutic Pathways, 2011)
Introduction: prophylaxis with granulocyte colony-stimulating factors (G-CSF) is indicated for reduction in the duration of neutropenia and the incidence of febrile neutropenia in patients treated with cytotoxic chemotherapy for malignancy. Objective: to evaluate the budgetary impact for the Italian NHS. Design: a decision-analytic model has been developed to analyze the budget impact from the national health care system perspective. Costs include direct healthcare costs to the public payer of G-CSFs as well as their administration costs and costs of FN-related events. The comparison has been done using prophylaxis with G‑CSF (filgrastim for 11 days, pegfilgrastim, lenograstim for 11 days) and antibiotics. Patients and participants: The population of interest for the analysis were patients with breast cancer in stage II and III and patients with non-Hodgkin’s lymphoma (NHL). Main outcome measures and results: for all the three patients group (NHL, Breast II and III), and for all the chemotherapy regimens (CHOP 21 and R-CHOP 21 for NHL, AC-T, TAC and TC for Breast stage II and III) the budget impact analyses shows a cost reduction for the Italian NHS, as a result of an increase of the use of pegfilgrastim. Conclusions: in Italy, a treatment strategy including pegfilgrastim as either primary or secondary prophylaxis provides value for money.